STRATEGI PEMENUHAN HAK WARGA NEGARA MENYAMPAIKAN PENDAPAT DALAM RANGKA DIGITAL CITIZENSHIP (STUDI PADA UNIT LAYANAN ADUAN SURAKARTA). - Lestyo Mawarti; Triana Rejekiningsih; Rima Vien P.H (Jurnal PPKn, 2019)
This study aims to find out: 1) Participation of citizens in submitting complaints through ULAS (Surakarta Complaint Service Unit); 2) Strategy for fulfilling the rights of citizens to express their opinions in the framework of digital citizenship through the ULAS 3) Obstacles to fulfilling the rights of citizens to express their opinions in the framework of digital citizenship through the ULAS This study uses qualitative research methods and descriptive research approaches. The research technique used was purposive and snowball sampling. Data collection uses interviews, observation and documentation. Testing data validity using data triangulation and methods. Data analysis uses an interactive analysis model. The results of this study include: 1) ULAS a forum for the people of Surakarta City to participate in providing public service complaints. In quantity, the people who participated through the ULAS were increasing. However, in quality there are still people who lack responsibility in using digital media, thus affecting the efficiency and effectiveness of ULAS; 2) The strategy for fulfilling the right to express opinions in the framework of digital citizenship by ULAS , a) providing websites, which are equipped with the provision of admin in each OPD (Regional Device Organization); b) socialization, to inform the public about ULAS; c) kelurahan facilitation, by providing admin in each kelurahan; d) availability of electronic forms for claimants each will submit a complaint; e) closure of complaints, by super admin for unclear complaints. The strategy implemented has embodied the community's right to participate in expressing opinions using digital media. But it still needs improvement in forming community responsibilities when it is more efficient and efficient; 3) Obstacles to fulfilling the right to express opinions carried out by ULAS include: a) internal barriers, namely there is still a manual system on the digital system, so that the super admin examines complaints closely every day to minimize errors in closing complaints and remaining admin OPD (Regional Device Organization) that has not been fluent in using technology, so that quarterly evaluations are carried out for the admin; b) external barriers include limited budgets and cessation of socialization, so socialization is carried out by only inviting figures close to the community to be able to convey back to other communities and insert material about the ULAS in every activity of government agencies.   Full Paper